2007
DOI: 10.1007/s10620-006-9476-7
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Lymphoid Aggregates in Slow Transit Constipation

Abstract: Information available on colonic lymphoid aggregates, apart from data of patients with inflammatory conditions, is scarce in other pathologic conditions. We investigated colonic lymphoid aggregates in patients with severe slow transit constipation, unresponsive to conventional therapeutic measures, and undergoing surgery for relief of their symptoms. Tissues from 27 patients with intractable slow transit constipation were obtained and compared with 10 controls. The number, diameter, lymphocyte distribution, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Surgery for constipation would normally be carried out on patients with the most refractory symptoms. In this review, 48 studies involving surgical treatment of constipation were included: 32 of which were surgical series, while 16 were studies on colonic tissue obtained at colectomy . Seven of the pathological series came from one center and three from another group …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery for constipation would normally be carried out on patients with the most refractory symptoms. In this review, 48 studies involving surgical treatment of constipation were included: 32 of which were surgical series, while 16 were studies on colonic tissue obtained at colectomy . Seven of the pathological series came from one center and three from another group …”
Section: Resultsmentioning
confidence: 99%
“…In this review, 48 studies involving surgical treatment of constipation were included: 32 of which were surgical series, 6,[14][15][16]21,[26][27][28][29][30][32][33][34][35]37,39,41,43,45,46,48,49,[51][52][53][54]56,[58][59][60]63 while 16 were studies on colonic tissue obtained at colectomy. [8][9][10][11][17][18][19][20]22,23,25,31,36,44,62,66 Seven of the pathological series came from one center 10,11,19,…”
Section: (Continues)mentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [ 18 ] used the iTRAQ labeling technique coupled with two-dimensional liquid chromatography-tandem mass spectrometry to analyze colon tissue from 43 patients with STC, and identified inflammatory cell infiltration. Villanacci et al [ 19 ] found that patients with intractable STC had a significantly greater number of colonic lymphoid aggregates than those in the control specimens. The number of colonic mast cells, a type of inflammatory cell, was shown to be elevated in severely constipated patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 But such prosaic observations would not have helped the lawsuits-for which Wakefield was hired before any child was referred, and which in the UK paid him more than £400 000. Five other Royal Free doctors-Davies and Dhillon were not among them-shared more than £100 000 to back him.…”
Section: Key Findings Omittedmentioning
confidence: 99%